Impact of Some Selected Determinants on SMEs Performance: A Study on Jhenaidah District of Bangladesh - Alam, Md. Ashraful; Shaikh, Md. Abdul Hannan (Archives of Business Research, 2023)
Small and Medium Enterprises (SMEs) play a critical role in any emerging economy. These sectors are now considered as the main engine of the economy in Bangladesh. The principal objective of this study is to identify, measure and compare the impact of some selected determinants on SMEs performance in Bangladesh. The study employed qualitative interviews with the owners/employees of SMEs dealing with i) Tailoring ii) Flower cultivation iii) Restaurant business iv) Auto rice mill business v) Jewelry vi) Nursery vii) Clinic business 8. Handicrafts business ix) Rice cultivation and x) Banana cultivation in Jhenaidah district of Bangladesh. This is a survey-based study and the data were collected from 101 respondents using a structured questionnaire. The data collected for the study have been processed using MS Excel 2007. This study examined six determinants such as entrepreneurial competency, marketing capability, financial resources, modern technology, product quality, and investment capacity to determine the SMEs’ performance in terms of profit. Seven hypotheses were developed to reach the objectives in the study. The collected primary data were analyzed by applying basic statistical tools. The results of the study revealed that the most significant determinants that affect the performance of SMEs in Bangladesh were entrepreneurial competency, financial resources and investment capacity respectively. Policymakers and owners of SMEs should take necessary steps in light of the findings of the study to improve the performance and ensure the sustainable growth of SMEs sectors in Bangladesh.